Konsekuensi ekologis pembalakan dalam kawasan hutan yang terbakar di Kalimantan Timur - Nieuwstadt, M.G.L. van; Kartawinata, K.; Sheil, Douglas (2002)
Results of a 2-year study on post-fire vegetation dynamics in the unlogged dipterocarp rainforest of Sungai Wain near Balikpapan East Kalimantan, Indonesia are discussed. Results showed that the maintenance of a productive permanent forest estate is likely to be served best by avoiding logging activities in burned areas.